PERENCANAAN SUMUR RESAPAN DAN PENGENDALIAN LIMPASAN DI WILAYAH SWAKARYA KELURAHAN SUKOREJO KOTA PAGAR ALAM - Eko Rachmad Iskandar; Fameira Dhiniati; Lily Endah Diansari (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2020)
The infiltration well will have the effect of reducing surface runoff. The rainwater that initially falls on the tile surface does not immediately flow to the drainage or yard of the house, but flows through zinc and continues to be collected into the infiltration well. The impact that can be felt is that rainwater does not spread into the yard or ditch, thereby reducing the occurrence of surface runoff. The purpose of this study way to calculate runoff discharge in the Swakarya area and plan the need for infiltration wells in the Swakarya area. Frequency method used the normal distribution method of gumbell distribution and log normal distribution. From the compatibility test using the Smirnov-Kolmogorov test, the results obtained were used the Gumbell method, while the value obtained war 131.10 mm with a period of 10 years. From the analysis, it rould be concluded that the planned flood discharge with a period of 10 years in the self-workshop area was 0,0001m3 / sec. The need for infiltration well for the self-contained area of ​​each housing unit requires an infiltration well with a diameter of 1 m and a depth of 0,625 m. Each infiltration well could accommodate a capacity of 0,639 m3